ON THE SOLUTION EXISTENCE OF COUETTE FLOW MODEL FOR SWIRLING FLOWS - Gangipelli Chandrashekhar; V. Ganesh; R. Thenmozhy; M. Chandrashekharan (Utilitas Mathematica, 2025)
We examine stability analysis of inviscid, hydromagnetic, incompressible flows with swirling motion. We derived general solution of the homogeneous problem in the case of Couette flow. We derived conditions for existence, non-existence of the series solutions for heterogeneous swirling flows. The results are depending on minimum Richardson number.